ABUSIVE CLAUSES (CIPEEX, 2025)
Introduction: Article 51 of the Brazilian Consumer Defense Code (CDC) declares null and void any contractual clauses that place consumers at an excessive disadvantage or are deemed abusive. Such clauses violate fundamental principles of the legal system, disrupt contractual balance, or restrict the exercise of essential rights. Objectives: This article aims to protect consumers against abusive contractual practices, ensuring fairness and balance in consumer relations. It also seeks to guarantee that illegal clauses may be annulled by the Judiciary, even without initiative from the parties involved. Materials and Methods: The analysis is based on current legislation and case law regarding the application of Article 51 of the CDC. Abusive clauses that limit consumer rights and undermine good faith and fairness in contractual relations are identified. Results: The following are considered abusive clauses: those that limit supplier liability; prevent reimbursement of amounts paid; impose a choice of forum that restricts access to justice; authorize unilateral changes to the contract; require compulsory arbitration; or unfairly transfer obligations to the consumer. Furthermore, under the principle of contract preservation, even when certain clauses are annulled, the remainder of the contract may be maintained, provided it does not harm the parties. Conclusion: Article 51 of the CDC plays a crucial role in consumer protection, ensuring fair and balanced contractual relations. The legislation seeks to safeguard consumer rights in the face of economic and technical vulnerability vis-à-vis suppliers, promoting social justice and dignity in private consumer relations.
Keywords: abusive clauses; Consumer Defense Code; good faith